(3GdGJUGd aj GdefXeGJ GdYGeI (B:s (3Hjf GdfXQjI h GdeeGQSI (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3eaghe GdGJUGd h eSJdReGJg , YedjI GdGJUGd h YfGUQgG , feGPL GdGJUGd , CfhGY GdGJUGd h fXQjGJg GdehbajI aj GdefXeGJ GdYGeI ,eYhbGJ GdGJUGd h CSGdjH eYGdLJgG aj GdefXeGJ GdYGeI , egGQGJ GdGJUGd aj GdefWeGJ GdYeI h GdeDSSGJ GdMchejI (B.s
(3eQGLY U(B.230s
Keywords: (3GdGJUGd `` GdefXeGJ GdYGeIs; (3GdYdGbGJ GdYGeIs; (3GdeDSSGJ GdMchejIs